Possible carcinogenic potential of dimethyl dimethoxy biphenyl dicarboxylate in experimental animals - Sanaa Sabet Botros; Naglaa Mohamed El-Lakkany; Olfat Ali Hammam; Abdel-Naser; Alaa Awad Taha (Wolters Kluwer Medknow Publications, 2016)
Dimethyl dimethoxy biphenyl dicarboxylate (DDB) has been extensively used in the treatment of liver diseases accounting for 1-6% of the global disease burden. Cell replication, DNA synthesis, and proliferation, providing significant information about behavior of cells were examined in mice exposed to subchronic administration with DDB. Conventional liver functions specifically gamma-glutamyltransferase (γ-GT), a marker expressing liver canceration was also investigated. Normal mice were allocated into two groups each of 10 mice. The 1 st and 2 nd groups were treated with DDB in a dose of 50 mg/kg/day, 5 days/week for 1 month and 3 months, respectively. Comparable groups of normal mice were left without treatment as controls. Compared to normal control group, animals receiving DDB for 3 months showed marked elevations of both alanine aminotransferase and γ-GT, significant inhibition in cytochrome P450, a significant increase in the mean ploidy and 4C with moderate to marked increase in S-phase populations and the number of proliferating cell nuclear antigen-positive cells. In conclusion, this is the first report on the potential relationship between the subchronic administration of DDB and the increase in the hepatocyte proliferation, cell replication and DNA synthesis that may raise an alarm regarding possible DDB insult on the biological behavior of cells.